Comparing talent development environments of girls and boys in handball and ice hockey in Norway - Mehus, I.; Martindale, R. J. J.; Andronikos, G.; Aspvik, N. P.; Bergström, M.; Sæther, S. A. (European Journal of Sport Science, 2025)
Currently, there is little research on successful talent development environments (TDEs) focusing on women and girls. In response, the main aim of the present study was to compare TDEs of age-specific national teams for girls and boys in the Norwegian context (N = 216: 92 girls and 124 boys). Gender differences were investigated in the two different sports of handball and ice hockey, which in the Norwegian context represent more and less successful sports (handball and ice hockey, respectively). Before investigating gender differences in the two sports, a necessary first step was to investigate the psychometric properties of Norwegian version of the Talent Development Environment Questionnaire (TDEQ-5). Results support the Norwegian TDEQ-5 to be a reliable and valid measure within the Norwegian context. The successful sport of Norwegian handball showed no significant gender differences regarding TDE. The less successful and male dominated sport of Norwegian ice hockey showed girls to score lower on several TDEQ factors compared to boys. Results also showed ice hockey having lower TDEQ scores compared to handball. We argue that handball provide similarly functional TDEs for girls and boys, making gender equality a characteristic feature of a TDE that is successful both in terms of mass participation and international achievements.